Hubungan Stres dan Adaptasi Akademik pada Mahasiswa Baru - Abednego Bagus Sariyono; Miftakhul Jannah; Rachman Widohardhono (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Some new students find it difficult to adapt to the college environment, new students are also more susceptible to stress, which can hinder their ability to adjust academically. The purpose of this study was to determine the relationship between stress and academic adaptation in new students. This study used a quantitative correlational methodology with a stress scale, the Depression Anxiety Stress Scale (DASS-stress) and an academic adaptation scale, the Student Adaptation to College Questionnaire (SACQ), both of which have undergone validity and reliability testing. Sampling used a purposive sampling technique obtained by 116 new students. The findings showed that the stress level of new students was in the moderate range and academic adaptation was high. Stress and academic adaptation produced significant positive values ​​in new students, according to the results of the Pearson correlation test (r = 0.744 with p < 0.001) and Spearman rho = 0.777 with p < 0.001. Based on the regression analysis, stress helped 55.3% of the variance in academic adaptation ability, with an R2 value of 0.553. In conclusion, there is a strong correlation between stress and academic adaptation in new students, so stress management techniques for new students are very necessary.